Breakdown of the coherence effects and Fermi liquid behavior in YbAl3 nanoparticles. (8th March 2018) - Echevarria-Bonet, C; Rojas, D P; Espeso, J I; Rodríguez Fernández, J; Rodríguez Fernández, L; Bauer, E; Burdin, S; Magalhães, S G; Fernández Barquín, L
Abstract: A change in the Kondo lattice behavior of bulk YbAl3 has been observed when the alloy is shaped into nanoparticles (≈12 nm). Measurements of the electrical resistivity show inhibited coherence effects and deviation from the standard Fermi liquid behavior ( T 2 -dependence). These results are interpreted as being due to the effect of the disruption of the periodicity of the array of Kondo ions provoked by the size reduction process. Additionally, the ensemble of randomly placed nanoparticles also triggers an extra source of electronic scattering at very low temperatures (≈15 K) due to quantum interference effects.